A tunable broadband filter of ternary photonic crystal containing plasma and superconducting material - Kumar A.; Thapa K.B.; Ojha S.P. (My University, 2025)
This work reports the optical properties of a one-dimensional (1D) ternary periodic structure composed of a dielectric, magnetized cold plasma (MCP) and superconducting material by using well-known simple transfer matrix method. The MCP has considered right-hand and left-hand polarizations having positive (+ B) and negative (− B) transverse magnetic field, respectively. The transmittance of the ternary photonic crystals is analyzed by varying the angle of incidence, the magnetic field, the electron density of the magnetized cold plasma, the temperature of the superconductor, the thickness of magnetized cold plasma and superconducting material for the right-hand and left-hand polarization structures. The transmittance of the ternary photonic crystal containing dielectric, magnetized cold plasma and superconducting material has tunable broadband and narrowband filters for the left-hand and right-hand polarizations, respectively. The magnetized cold plasma layer in the ternary photonic crystal also played an important role to form the tunable gap due to the transverse magnetic field. The analysis of the transmittance of the ternary photonic crystal containing dielectric, magnetized cold plasma and superconducting materials has shown an innovative idea for the formation of the tunable broadband and the narrowband filters. © 2018, Indian Association for the Cultivation of Science.